(untitled) (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2015)
Improving cocoa quality through encouraging farmers to do fermentation is one of the ways to increase the added value of cocoa. However, majority of Indonesian farmers are reluctance to do fermentation. This research aimed to study factors causing farmers reluctant to do fermentation, weight difference between fermented and unfermented cocoa, cocoa processing time difference between fermented and unfermented cocoa, quality difference between fermented and unfermented coco refers to cocoa bean standard (SNI): 01-2323-2008/Amd-2010, and feasible added value incentive of fermented cocoa beans. The data collection were conducted through household farmers’ survey, focus group discussion and experimental research. The experimental research was conducted to understand the weight and processing time differences; and to asess the quality, including moisture content, bean count, pH and fermentation index. Analysis of the data were conducted by methods of Fishbone Ishikawa and logit multiplier linear analysis. The research results showed that the main factors causing farmers reluctant to do fermentation were insuitable of selling price of fermented cocoa, the existence of village collectors in buying unfermented cocoa, the lack of cooperation among farmers in farmer group (Subak Abian) and the lack of farmers’ skills on cocoa bean fermentation. This study also found that the weight depreciation difference between fermented and unfermented cocoa was 0.5-3.75%, and the processing time difference between fermented and unfermented cocoa was 12-24 hours. Quality of fermented cocoa beans was higher than that of unfermented cocoa beans and it can fulfill the standard of SNI: 01-2323-2008/Amd-2010. It was found that the feasible added value incentive of fermented cocoa benas was 2,126-3,426 IDR/kg. Keywords: cocoa, fermentation, unfermented, quality, incentive